PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT PELABUHAN INDONESIA III (PERSERO) OPERATOR TERMINAL PETI KEMAS SEMARANG (TPKS) - Hani Rahma Ardhani; Sri Suryoko (Universitas Diponegoro, 2018)
All companies want high employee performance, with the hope of potentially bringing benefits to the company. The contribution of human resources to a company is very strategic. Through influencing variables including leadership and Organizational Culture. Based on existing problems in this research is the decrease of employee performance of PT Pelabuhan Indonesia III (Persero) Container Terminal (Semarang) in year 20162017 on achievement of box production employee of TPKS operator. The purpose of this study is to determine the influence of leadership and Organizational Culture on employee performance PT Pelabuhan Indonesia III (Persero) Container Terminal (Semarang).This type of research is explanatory research, with a population of 74 respondents employees of PT Pelabuhan Indonesia III (Persero) Container Terminal (Semarang). Sampling in this study using saturated sampling. Data analysis method used validity test, reliability test, correlation coefficient, simple regression analysis, multiple regression analysis, determination coefficient, and significance test (t test and f test) using SPSS application.This study concluded that leadership and Organizational Culture have a positive effect on employee performance. Leadership variables have bigger influence from Organization Culture variable. Based on this, the researcher suggested the company to pay attention to the work environment factor where the work environment in the engineering section requires team cooperation between superior and good subordinates so that employees can complete their tasks while working in the field.